The vibroacoustical indexes of the internal combustion engine when the mass of the details of the crankshaft device varies - Juodzevičius, Eimantas; Valičnas, Valdas (Transport, 2002)
The vibroacoustical indexes of the intemal combustion engine retrogress when the mass of the details of the crankshaft device increases. The blatancy of sound pressure, oscillation speed, the whole engine increase very fractionally when mass increases from 0,5 to 16,0 g. This phenomenon increases loads which affect the principal bearings of the crankshaft as well as the uneven distribution of the loads.First Published Online: 19 Dec 2011